ANALYSIS OF THE LIMITS OF AUTHORITY OF GENERAL PRACTITIONERS IN COMMUNITY HEALTH CENTERS IN ISSUING VISUM ET REPERTUM BASED ON LAW NO. 17 OF 2023 ON HEALTH - Jaya Ashari; Herlita Eryke; Marlis Tarmizi (SOSIOEDUKASI, 2026)
Visum et Repertum (Visum et Repertum) plays a crucial role in the criminal evidence process, but the authority of general practitioners in community health centers (Puskesmas) to issue them still creates legal uncertainty, especially after the enactment of Law Number 17 of 2023 concerning Health. This study aims to analyze the limitations of general practitioners' authority in preparing visums based on provisions of health law and state administrative law. The research method used is normative juridical, with a statutory, conceptual, and doctrinal approach, accompanied by an analysis of forensic medicine literature and medical professional regulations. The results indicate that Law 17 of 2023 does not explicitly regulate the authority of general practitioners in forensic procedures. Therefore, visums can only be issued if they comply with competency, professional standards, and the medical code of ethics. The study also found a gap between the needs of law enforcement in the regions and the limited forensic personnel, resulting in general practitioners still being required to issue visums despite inadequate normative basis. The study's conclusions emphasize the need for more comprehensive derivative regulations to provide legal certainty, improve the quality of visums, and protect doctors from legal risks.